Analisis Yuridis Perbuatan Wanprestasi dalam Jual Beli Secara Online : Studi Putusan Nomor 151/Pdt.G/2020/PN Jakarta Selatan - Marlina Elisabeth Pakpahan; Tasya Miana Putri Br. Sinurat; M. Fachrur Rozi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This study aims to legally analyze breach of contract in online buying and selling based on Decision Number 151/Pdt.G/2020/PN South Jakarta. The research is motivated by the increase in electronic transactions that have the potential to cause breach of contract due to failure to fulfill obligations by the parties. The method used is normative juridical with a statutory and conceptual approach and is descriptive analytical in nature. Legal materials include the Civil Code, the Electronic Information and Transactions Law (UU ITE), the Consumer Protection Law, and related court decisions. The results of the study indicate that the elements of breach of contract in online transactions still refer to civil law, namely the existence of a valid agreement, negligence in fulfilling obligations, losses, and a causal relationship between negligence and losses. In the decision, the judge stated that the legal relationship between the parties remains valid even though the agreement was made electronically without a formal written contract. The defendant was deemed to have committed breach of contract because he did not fulfill his obligations to send goods and hand over the proceeds of COD payments. The regulation of breach of contract in online transactions is an integration of the Civil Code, the ITE Law, and the Consumer Protection Law. Legal consequences include compensation, fulfillment of performance, or cancellation of the agreement. Furthermore, electronic documents are recognized as valid evidence in cases of breach of contract.